Edukasi dan Simulasi Proses Pembuatan Tepung Daun Singkong di Desa Kedungpangan Sidoarjo - Saidi, Ida Agustini; Budiandari, Rahmah Utami; Azara, Rima; Nurbaya, Syaraifa Ramadhani (Universitas Muhammadiyah Malang, 2025)
Purpose – The purpose of this activity is to provide knowledge and skill of Kedung Pandan’s people in optimizing the diversification of cassava leaf processed into flour. Design/methodology/approach – The implement methods includes presentation, discussions, training and mentoring programs including training on the process of making dodol and applicaton of Good Manufacturing Practices or GMP, an evaluation stage. Findings – Training activities are conducted by producing outpus such as seaweed porridge processing techniques, packaged dodol products. The evaluation results show the high desire of Kedung pandan village’s people to develop seaweed, that easy to find but innovation and creation are still needed so the product can become icon of Desa Wisata Bahari Tlocor. Originality/Value – Through this community service, we can diversify seaweed, add value added of seaweed and created a snack icon for the Desa Wisata Bahari Tlocor.